Extractives from six species of South African Marine Opisthobranch Molluscs - McPhail, Kerry Lee (Rhodes University, Faculty of Science, Department of Chemistry, 2001)
The natural product chemistry of six species of South African opisthobranch molluscs and some of their dietary marine invertebrates was investigated. Nineteen previously undescribed secondary metabolites and twelve known compounds were isolated and their structures determined by a combination of spectroscopic and chemical methods. The circumtropical sea hares Aplysia parvula and A. dactylomela were found to contain halogenated red algal metabolites. 3Z-bromofucin (120), the Z analogue of a known Laurencia CIS acetogenin, was isolated from A. parvula. A. dactylomela yielded a series of novel non-aromatic cuparanes, the algoanes (121-123), the novel tricyclic Iaurane ether ibhayinol (124) and three known chamigrane sesquiterpenes, prepacifenol epoxide (101), pacif-7-enediol (104) and nidificene (125). A variety of new octocoral sesquiterpenes were isolated from the endemic South African arminacean nudibranch Leminda millecra including algoafuran (150), cubebenone (151), 8-hydroxycalamenene (152) and a series of seven triprenylated toluquinones and toluquinols (153-159). L. millecra also yielded the known sesquiterpenes millecrones A (142) and B (143) and isofuranodiene (149). Twenty eight voucher specimens and eighteen crude extracts of South African octocorals collected by the Coral Reef Research Foundation were screened by GC and GC-MS and 142 was found in Alcyonium fauri, while 143, 151 and possibly 149 were present in Leptogorgia palma. An investigation of southern African chromodorids yielded the known macrocyc1e latrunculin B (220) and two new spongiane diterpenes (221) and (222) from Chromodoris hamiltoni, while the known spongiane diterpene (210) was isolated from the endemic nudibranch Glossodoris sp. 4. The endemic nudibranch Hypselodoris capensis contained the known furanosesquiterpenes nakafuran-8 (223) and -9 (224) and the known furanosesterterpenes variabilin (195), 22-deoxyvariabilin (225) and furospinosulin (227) together with the new variant 22-deoxy-23-hydroxymethylvariabilin (226). Compounds 223 and 224 were also found in a Dysidea sponge, while the furanosesterterpenes 195, and 225-227 were present in a Fasciospongia sponge upon which H capensis specimens were found. The Dysidea dietary sponge of H capensis also yielded a new aromatic sesquiterpene, tsitsikarnmafuran (266), whose structure was confirmed by the synthesis of two possible regioisomers.
Keywords: Mollusks -- Nutrition; Mollusks -- Anatomy; Marine fishes -- South Africa